Trends in global inequality using a new integrated dataset - Carlos Gradín (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper presents preliminary evidence of the annual global income distribution since 1950 using a new integrated dataset that aggregates standardized country income distributions at the percentile level estimated from various sources in the World Income Inequality Database. I analyse the extent to which the main global inequality trends depend on specific distributive views, i.e. absolute or relative, or with more emphasis in specific parts of the distribution. The results show absolute inequality increasing almost continuously. Relative inequality has been clearly reduced in the long term but with most indices also showing a sharp decline since at least end of 1990s due to income differences between countries being narrowed. I also quantify the contribution of different countries and regions through changes in average income, in inequality or in population, showing that the main global trends are largely driven by the drastic changes experienced by China and India over these decades.
Keywords: D31; D63; I31; O15; 330; global inequality; income distribution; World Income Inequality Database